Palliative interventions in outpatient dialysis network - Branco,Ana (2020)
Chronic kidney disease (CKD) is a burdensome disease that has been successfully managed with dialysis. But even if dialysis can prolong patients' survival in certain circumstances, it also brings a high burden of physical and psychosocial symptoms, poor outcomes, and high costs of care. Fragile patients may not benefit from starting dialysis. In this way, Palliative Care (PC) should be integrated into CKD care to control symptoms' burden, to discuss the shared decision to start or forgo dialysis when stage 5 CKD approaches, or to select conservative management of end-stage renal disease (ESRD) or withdrawal dialysis. As patients attended in private hemodialysis units get older and more fragile, incorporation of PC is associated with the highest quality care standards provided to our ESRD patients. That being so, we designed a project based on the World Health Organization (WHO) recommendations to implement palliative interventions in NephroCare Hemodialysis Units. In our project, we consider the following five steps: (i) assessment of palliative needs in dialysis patients; (ii) team education; (iii) contact and referral to specialized teams; (iv) registration (v) and trial of the pilot project. We also reflect on the barriers to implementation of this project. This article aims to raise awareness of the project and use it as a model or a first step to other projects in the actual area to be implemented in other health units.